A characterization of the generalized Meijer transform - E. Y. Deeba; E. L. Koh (International Journal of Mathematics and Mathematical Sciences)
The purpose of the note is to prove a representation theorem for the generalized Meijer transform defined in [2]. In particular, we shall state and prove necessary and sufficient conditions for a function F(p) to be the generalized Meijer transform of a generalized function.